Reform of reduced earning capacity pension cuts risk of poverty, but comes late - Sebastian Becker; Annica Gehlen; Johannes Geyer; Peter Haan (DIW Weekly Report, 2023)
An accident, a chronic illness, or even a congenital disability are common causes of a loss of earning capacity. Although the loss of earned income is insured through the reduced earning capacity pension in the statutory pension insurance scheme, the amount received is so low that people with reduced earning capacity are at very high risk of poverty and there is a higher-than-average likelihood of them claiming basic income support. Since the 2001 pension reform, there has been a general decrease in average benefit payments. Reforms in 2014 and 2019 introduced improvements to new pensions but existing pensions did not benefit. The reform aims to correct this from July 2024. Calculations show that although this reform could potentially reduce the risk of poverty by around eight percent, there continues to be an above-average likelihood of people with reduced earning capacity being affected by poverty. In addition, those affected have a low life expectancy, meaning that a significant portion of those who could potentially benefit from the reform will no longer be alive when it comes into force. The findings show that the changes need to be implemented quickly and other measures are required to minimize the risk of poverty among those with reduced earning capacity. – – Ein Unfall, eine chronische Erkrankung oder auch eine angeborene Behinderung sind häufige Ursachen für den Verlust der Erwerbsfähigkeit. Der Wegfall des Erwerbseinkommens wird zwar durch die Erwerbsminderungsrente in der gesetzlichen Rentenversicherung versichert. Diese Rente ist aber so niedrig, dass Erwerbsgeminderte einem sehr hohen Armutsrisiko ausgesetzt sind und überdurchschnittlich häufig Leistungen der Grundsicherung beziehen. Seit der Rentenreform 2001 sind die durchschnittlichen Leistungen stark zurückgegangen. Reformen in den Jahren 2014 und 2019 führten zwar Verbesserungen für neu zugehende Renten ein, der Rentenbestand profitierte allerdings nicht davon. Dies wird erst zum Juli 2024 nachgeholt. Berechnungen zeigen, dass diese Reform das Armutsrisiko zwar um knapp acht Prozent senken kann, Erwerbsgeminderte aber weiterhin überdurchschnittlich häufig von Armut betroffen sind. Zudem haben die Betroffenen eine niedrige Lebenserwartung; ein relevanter Teil der potenziell Begünstigten wird nicht mehr am Leben sein, wenn die Reform in Kraft tritt. Die Ergebnisse verdeutlichen, dass es bei dieser Leistung auf eine schnellere Umsetzung ankommt und weitere Maßnahmen nötig sind, um das Armutsrisiko bei Erwerbsminderung zu reduzieren.
Keywords: D31; H55; I14; 330; disability pension; poverty; pension reform